Sinergity of Village Owned Enterprises and MSMEs in Upgrading Daergic Potentials: Study on Sido Makmur Village, Getasan Village, Getasan District, Semarang Regency - Prasetyo Suryahadi Mahendra Lisaputra; Linda Kusuma (Borong Newinera Publisher, 2024)
Getasan Village has strategic potential and sufficient resources to advance Micro, Small and Medium Enterprises (MSMEs). The village's vision and mission, enshrined in Village Regulation No. 2/2019, focuses on the development of MSMEs. Although most MSMEs in the village still operate on a small and home-based scale, they remain a pillar of the local economy. However, challenges such as limited capital, lack of management knowledge, less supportive infrastructure, as well as limited market access hinder the growth of MSMEs. To address this, Village-Owned Enterprises (BUM Desa) are considered a potential solution. Law No. 6/2014 on Villages provides a legal foundation for the establishment of BUM Desa. With the synergy between BUM Desa and MSMEs, local economic potential can be maximized. The research used participatory observation methods and a qualitative approach. The results show several patterns of effective synergy between BUM Desa and MSMEs, such as capital strengthening, infrastructure development, skills training, and joint promotion. These measures are expected to improve the competitiveness and growth of MSMEs and provide positive impacts for the government and community. The formulation of BUM Desa's strategy in utilizing local economic potential and mobilizing MSMEs is also detailed to provide direction for further development.